2021
DOI: 10.32832/pro.v4i5.5657
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Penyebab Pengembalian Berkas Klaim Pasien Badan Penyelenggara Jaminan Sosial (Bpjs) Kesehatan Pada Layanan Rawat Jalan Tingkat Lanjut (Rjtl) Di Rumah Sakit Paru Dr. M. Goenawan Partowidigdo Tahun 2019

Abstract: <p>Pada tahun 2018 dan 2019 terdapat berkas klaim pasien rawat jalan`yang dikembalikan oleh BPJS kesehatan kepada Rumah Sakit Paru Dr. M. Goenawan Partowidigdo yaitu sebanyak 892 berkas klaim pada tahun 2018 sedangkan pada tahun 2019 sebanyak 417 berkas klaim pasien yang dikembalikan. Penelitian ini bertujuan untuk mengetahui penyebab pengembalian berkas klaim pasien BPJS kesehatan rawat jalan dengan menggunakan kualitatif deskriptif dengan pengumpulan data melalui wawancara mendalam, observasi dan telaa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Outpatient claims data submitted and returned are as follows in Table 1: The number of outpatient claim documents for RS X South Tangerang returned by BPJS Health in the table above is 3795 claim files or approximately 3.2% of the total claim documents submitted. Research at Singaparna Medika Citrautama Hospital in 2014 found 476 rejected files from 9815 outpatient claims submitted or approximately 4.8% [4], while in research at the Pulmonary Hospital, Dr. M. Goenawan Partowidigdo who sent as many as 6895 patient claim documents for outpatient services to BPJS Health in 2019, and there were 448 patient claim documents submitted by hospitals that were returned by BPJS Kesehatan [5].…”
Section: Number Of Claim Documents Returnedmentioning
confidence: 99%
See 1 more Smart Citation
“…Outpatient claims data submitted and returned are as follows in Table 1: The number of outpatient claim documents for RS X South Tangerang returned by BPJS Health in the table above is 3795 claim files or approximately 3.2% of the total claim documents submitted. Research at Singaparna Medika Citrautama Hospital in 2014 found 476 rejected files from 9815 outpatient claims submitted or approximately 4.8% [4], while in research at the Pulmonary Hospital, Dr. M. Goenawan Partowidigdo who sent as many as 6895 patient claim documents for outpatient services to BPJS Health in 2019, and there were 448 patient claim documents submitted by hospitals that were returned by BPJS Kesehatan [5].…”
Section: Number Of Claim Documents Returnedmentioning
confidence: 99%
“…This causative factor also occurs in filing claim documents at the Lung Hospital, Dr. Goenawan Partoidigdo, where the claim file was returned due to an error in entering hospital class rates, repeated control indications, and the absence of supporting examination reports [5].…”
Section: Factors Causing Claim Documents Returnedmentioning
confidence: 99%
“…Several studies have used decision support systems such Fuzzy method is also widely used in analyses related to environmental quality, such as river water quality classification [7], air quality monitoring [8], room temperature control performance evaluation of fertilizer tools [9], to grouping areas based on environmental health indices [10]. Meanwhile, the ISM method is widely used to determine key elements of management or policy strategies related to environmental issues, including post-pandemic ecotourism management [11], determination of elements of integrated crop actors in sustainable agriculture [12], institutional analysis of sustainable situ management of institutional strategies for independent oil palm smallholders [13], and analysis of community sector elements due to green logistics rubber agroindustry [14].…”
Section: Introductionmentioning
confidence: 99%